Water-dispersible graphene/polyaniline composites for flexible micro-supercapacitors with high energy densities. (September 2015) - Song, Bo; Li, Liyi; Lin, Ziyin; Wu, Zhen-Kun; Moon, Kyoung-sik; Wong, Ching-Ping
Abstract: Lightweight and mechanically compliant energy storage devices have attracted tremendous interest due to the increasing demand for flexible and miniaturized electronics. Recently, micro-supercapacitors (MSCs) have advanced rapidly as potential micro-sized power sources, but it is still challenging to build the micro-device using cost-effective technologies for large-scale manufacture. Here, we developed a simple solution-processible method to fabricate microelectrode patterns using a water-dispersible graphene/sulfonated polyaniline (rG/SP) as the active MSC material. The highly stabilized rG/SP dispersion in aqueous solution enables the direct thin-film deposition on flexible substrates and the formation of interdigital patterns by plasma etching. The as-fabricated solid-state MSC delivers an ultrahigh areal capacitance of 3.31 mF/cm 2 and volumetric stack capacitance of 16.55 F/cm 3 with excellent rate and cycling performance. Furthermore, the rG/SP based MSC demonstrates a superior energy density of 1.51 mW h/cm 3 while maintaining high power density. The micro-device also shows superior mechanical stability with 96.5% of capacitance retained under different bending and twisting conditions, which makes it suitable specifically for portable and wearable electronic applications. Graphical abstract: Highlights: A solution-processible method to fabricate MSC electrodes with direct thin film deposition. The rG/SP electrode material is highly conductive and aqueous dispersible. Formation of interdigital patterns via shadow masking and plasma etching. The device shows superior energy density, cycling and electromechanical stability.